Correlation of maternal body mass index with umbilical artery Doppler in pregnancies complicated by fetal growth restriction and associated outcomes. Issue 2 (12th February 2021) - Cody, Fiona; Mullers, Sieglinde; Flood, Karen; Unterscheider, Julia; Daly, Sean; Geary, Michael; Kennelly, Mairead; McAuliffe, Fionnuala; O'Donoghue, Keelin; Hunter, Alyson; Morrison, John; Burke, Gerard; et al.
Abstract: Objective: To evaluate the correlation between umbilical artery (UA) Doppler and its feasibility across categories of maternal body mass index (BMI; calculated as weight in kilograms divided by the square of height in meters) in the presence of fetal growth restriction (FGR). Methods: A total of 1074 singleton pregnancies with suspected FGR on ultrasound examination between 24 +0 and 36 +0 weeks of pregnancy were reviewed. Evaluation of the UA Doppler was performed at 1‐ to 2‐weekly intervals. Abnormal UA Doppler findings and delivery outcomes were compared between the different maternal BMI categories. Results: Increased UA pulsatility index (PI >95th centile) was reported in 81% of obese class II patients (BMI 35–39.9) compared with a 46% incidence in the remaining categories, normal (BMI <24.9), overweight (BMI 25–29.9), and obese class I (BMI 30–34.9) ( P  = 0.001). In absent or reversed end diastolic flow (AEDF/REDF) we found an increasing incidence across the BMI categories (4%–25%) ( P  < 0.001). Higher maternal BMI was associated with lower birthweights and higher cesarean section rates. Increasing maternal BMI did not affect successful assessment of UA Doppler. Conclusion: There is a positive correlation between increasing maternal BMI and abnormal UA Doppler findings in FGR. Maternal BMI may be considered as an additional risk factor when evaluating UA Doppler for placental insufficiency. Synopsis: Maternal BMI correlates with abnormal umbilical artery (UA) Doppler findings and outcomes in growth‐restricted babies but does not affect feasibility of UA Doppler.